Geographical and Temporal Changes of Reef Fish (Labridae) Assemblages: A Case Study of South Western Australia - Parker, Jack Ryan Cripps (Curtin University, 2019)
Changes in Labridae assemblages and distributions along South Western Australia’s (SWA) coastline were investigated over 10 years of climate change. This study found district assemblage composition changes, with an inundation of warm water associated species and functional groups and a corresponding decline in large bodied cool water species. This thesis identified unprecedented marine assemblage changes in SWA and forms a platform for future research to further manage the unique SWA ecosystem.